ORGANIZATIONAL INNOVATION IN MEDIATING TRANSFORMATIONAL LEADERSHIP TO ORGANIZATIONAL PERFORMANCE - Handayani, Evi; Syawaludin, Syawaludin; Yuslinda, Yuslinda; Herlambang, Wira (CV. Radja Publika, 2022)
This research aims to see the effect of transformational leadership on the performance of the organization in the office of the Border Management Department of the Regional Secretariat of Karimun Regency mediated by Inovasi. This study is a quantitative study that uses a sample of 60 respondents. Data analysis using Structural Equation Modeling (SEM) analysis with Smart PLS 2.0 software. The results showed that: (1) Innovation has a positive and significant effect on the performance of the organization in the office of the Border Management Department of the Regional Secretariat of Karimun Regency, seen from the value of t values 2,589 greater than the standard set at 1.96, (2) Transformational Leadership has a positive and significant effect on Innovation in the office of the Border Management Department of the Regional Secretariat of Karimun Regency with a value of t values of 38,004, (3) Transformational Leadership has a positive and significant effect on the performance of the organization in the Office of Border Management Section of the Regional Secretariat of Karimun Regency with t values of 13,525, (4) Transformational leadership has a positive and significant effect on the performance of the organization in the office of the Border Management Department of the Regional Secretariat of Karimun District mediated by Innovation with a value of t values of 40,493.